The Risk Perception as a Mediator Between Herding and Overconfidence on Investment Decision by Gen Z in Indonesia - Kaban, Lila Maria; Linata, Evita (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2024)
Behavioral finance theory highlights how psychological factors can lead to poor investment decisions, which may threaten investors' trust in the stock market, discourage investments, and hinder economic growth. This study aims to examine how behavioral finance factors, particularly herding bias and overconfidence bias, influence investment decision on the Indonesia Stock Exchange through risk perception. The research was conducted using an online questionnaire distributed to 120 Gen Z stock investors and analyzed using PLS-SEM. The results show that herding and overconfidence biases have a significant positive influence on risk perception. Both herding and overconfidence biases have indirect positive influences on investment decision through risk perception. Although overconfidence bias and risk perception can directly affect investment decision, herding bias fails to do so. These findings highlight the importance of considering an individual's behavioral biases and risk perception, while policymakers should devise strategies to mitigate their impacts; so that investors can benefit from investing, which may eventually lead to the growth of the national economy